Europe's clean technology investment challenge - Reinhilde Veugelers (Bruegel, 2011)
Development and deployment of clean-energy technologies is crucial if climate targets are to be met cost-effectively. The European Union already has a plan that deals with these issues: the Strategic Energy Technology Plan, which has become central to the achievement of the EU's ambitions. In a period of constrained public finances, if governments want to leverage the necessary private innovation for clean-energy technologies, they will have to provide well-designed time-consistent policies, reducing commercial and financial risk through a combination of consistent carbon pricing, regulations and public funding, which will have to give a sizable and consistent push to early-stage clean-energy technologies, with a clear exit strategy. But first and foremost, governments should establish a sufficiently high and long-term predictable carbon price. The design of the EU emissions trading system and the distribution of carbon allowances should take into account more explicitly its power to leverage innovation. A move to a 30 percent EU emissions reduction target, which would involve a tighter emissions cap and fewer allowances being auctioned, would result would result in a higher carbon price and provide greater incentives for innovation.
Keywords: 330; Klimaveränderung; Umweltpolitik; Ökosteuer; Investitionspolitik; Regenerative Energie; EU-Staaten